(untitled) - Nielsen, Jennifer A. (New York, 2019)
In 1893 twelve-year-old Audra lives on a farm in Lithuania, and tries to avoid the Cossack soldiers who enforce the Russian decrees that ban Lithuanian books, religion, culture, and even the language; but when the soldiers invade the farm Audra is the only one who escapes and, unsure of what has happened to her parents, she embarks on a dangerous journey, carrying the smuggled Lithuanian books that fuel the growing resistance movement, unsure of who to trust, but risking her life and freedom for her country.
Keywords: Smuggling; Fiction; Adventure and adventurers; Interpersonal relations; Fiction; Government, Resistance to; Fiction; Books and reading; Fiction; Smuggling; Fiction; Juvenile fiction; Interpersonal relations; Juvenile fiction; Government, Resistance to; Juvenile fiction; Books and reading; Lithuania; Juvenile fiction; Adventure stories; History; Fiction; Lithuania; 19th century; History; Fiction; Lithuania; 19th century; Juvenile fiction; Lithuania; History; Juvenile fiction; Lithuania; History; Action and adventure fiction